Analisis Penggunaan Teknik Terjemahan Transposisi pada Novel Klasik Terjemahan “Puri Pictordu” - Fadhilah, Nurul Maura; Gumilar, Dudung; Mulyadi, Yadi (Stilistika: Jurnal Pendidikan Bahasa dan Sastra, 2025)
This study focuses on the analysis of the use of translation techniques by the translator in the translated novel "Puri Pictordu" by the translator Reinitha Amalia Lesmana in 2021 from the French novel "Le Château de Pictordu (1873) by George Sand. This study have purpose for describe the transposition technique in translation that used in the novel and describe the effects on the translation results. Descriptive qualitative is the research method that used in this study to analyze and explain the discovery of the types of transposition translation techniques in this translated novel and explain them in sentences regarding their acceptability. The results of the study show that 147 data found in this translated novel. There are 135 acceptable translation data and 12 unacceptable translation data as the translator translated them. Transposition translation focuses on structural shifts that are adjusted to the grammar of the target language. The focus of the transposition translation used by the translator makes some of the translation results still feel like translated sentences.